Can pictures promote the acquisition of sight‐word reading? An evaluation of two potential instructional strategies. Issue 1 (30th September 2016) - Richardson, Amy R.; Lerman, Dorothea C.; Nissen, Melissa A.; Luck, Kally M.; Neal, Ashley E.; Bao, Shimin; Tsami, Loukia
Abstract : Sight‐word instruction can be a useful supplement to phonics‐based methods under some circumstances. Nonetheless, few studies have evaluated the conditions under which pictures may be used successfully to teach sight‐word reading. In this study, we extended prior research by examining two potential strategies for reducing the effects of overshadowing when using picture prompts. Five children with developmental disabilities and two typically developing children participated. In the first experiment, the therapist embedded sight words within pictures but gradually faded in the pictures as needed using a least‐to‐most prompting hierarchy. In the second experiment, the therapist embedded text‐to‐picture matching within the sight‐word reading sessions. Results suggested that these strategies reduced the interference typically observed with picture prompts and enhanced performance during teaching sessions for the majority of participants. Text‐to‐picture matching also accelerated mastery of the sight words relative to a condition under which the therapist presented text without pictures.